2013
DOI: 10.1136/bmjopen-2013-003876
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of access to services in a random sample of Canadian rural emergency departments

Abstract: ObjectiveTo examine 24/7 access to services and consultants in a sample of Canadian rural emergency departments (EDs).DesignCross-sectional study—mixed methods (structured interview, survey and government data bases) with random sampling of hospitals.SettingCanadian rural EDs (rural small town (RST) definition—Statistics Canada).Participants28% (95/336) of Canadian rural EDs providing 24/7 physician coverage located in hospitals with acute care hospitalisation beds.Main outcome measuresGeneral characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 29 publications
0
45
2
Order By: Relevance
“…However, 67% of rural women deliver in urban hospitals: 17% are more than 120 min driving distance from their hospital of birth [20]. It must also be noted that even when hospital emergency departments exist in rural and remote locations, they do not always provide the whole range of services and do not always have the same wealth of resources and equipment as urban emergency departments [21].…”
Section: Canadamentioning
confidence: 99%
“…However, 67% of rural women deliver in urban hospitals: 17% are more than 120 min driving distance from their hospital of birth [20]. It must also be noted that even when hospital emergency departments exist in rural and remote locations, they do not always provide the whole range of services and do not always have the same wealth of resources and equipment as urban emergency departments [21].…”
Section: Canadamentioning
confidence: 99%
“…If advanced imaging is required, 44% of these rural EDs would need to transfer their patients upwards of 300 km to a nearby trauma centre resulting in significant delays to definitive care. 3 This is even more concerning in the context of rural residents having a higher prevalence of acute and chronic illness as well as greater risk for trauma and trauma death compared to their urban counterparts. 4,5 A potential solution may exist with an imaging modality that is cost-effective, noninvasive, easily accessible, contrast-free, requires no special preparation of the patient, decreases time to diagnosis, 6 decreases patient ED length of stay, 7 decreases time to operative care, 8 and improves acute care outcomes 9 -that is, point-of-care ultrasound (PoCUS).…”
Section: Introductionmentioning
confidence: 99%
“…For example, only 5% of hospitals had access to a paediatrician, 26% had access to a surgeon and less than one-third had access to ultrasound equipment (28%), a computerised tomography scanner (20%) or an intensive care unit (17%). 53 Studies of community hospitals in England and Scotland typically reported on the provision of non-acute inpatient services, particularly post-acute geriatric care, rehabilitation services and palliative care. 7,[54][55][56][57][58] Indeed, several UK community hospitals provide exclusively, or largely, non-acute inpatient care to chronically ill or older populations.…”
Section: Range Of Services Provided By Community Hospitalsmentioning
confidence: 99%